Kemampuan Mengenal Angka Melalui Media Gambar Asosiatif - Rambe, Syarifah Ainy; Konadi, Husrin (Jumper: Journal of Educational Multidisciplinary Research, 2022)
Early childhood is a golden age where at this time children are expected to get learning lessons in order to improve their cognitive abilities in the future. Improve children's cognitive including recognizing numbers. Number recognition is very important starting from an early age, but in reality there are many children aged 4-5 years who do not know the numbers 1-10. The purpose of this study was to help early childhood in introducing numbers 1-10 using associative image media. This research was conducted on children aged 4-5 years in Reje Guru Village, Bener Meriah, Aceh, a total of 7 people. The results of this study before being given associative picture learning, children are still not able to recognize numbers perfectly, after that they are given a lesson to introduce numbers 1-10 using associative picture media in children for 2 months, then the test is carried out again to 7 children who are the research sample, and the result is that the child is able to recognize numbers well, the child is able to say the numbers in sequence and the child is able to name the randomly designated numbers.